Dynamic knee valgus kinematics and their relationship to pain in women with patellofemoral pain compared to women with chronic hip joint pain - Eric Schmidt; Marcie Harris-Hayes; Gretchen B. Salsich (Journal of Sport and Health Science, 2019)
Background: Dynamic knee valgus (DKV) is an abnormal movement pattern visually characterized by excessive medial movement of the lower extremity during weight bearing. Differences in hip and knee kinematic components of DKV may explain the emergence of different pain problems in people who exhibit the same observed movement impairment. Using a secondary analysis of exiting data sets, we sought to determine whether hip and knee frontal and transverse plane angles during a functional task differed between women with patellofemoral pain and women with chronic hip joint pain and the relationship between joint-specific kinematics and pain in these 2 pain populations. Methods: In the original studies, 3-dimensional hip and knee kinematics during a single-limb squat were obtained in 20 women with patellofemoral pain and 14 women with chronic hip joint pain who demonstrated visually classified DKV. Pain intensity during the squat was assessed in both groups. For the secondary analysis, kinematic data were compared between pain groups using their respective control groups as a reference. Within each pain group, correlation coefficients were used to determine the relationship between kinematics and pain during the squat. Results: Hip adduction and contralateral pelvic drop were greater in those with chronic hip joint pain compared to those with patellofemoral pain (effect sizes ≥0.40). Greater knee external rotation (r = 0.47, p = 0.04) was correlated with greater knee pain in those with patellofemoral pain, while greater hip adduction (r = 0.53, p = 0.05) and greater hip internal rotation (r = 0.55, p = 0.04) were correlated with greater hip pain in those with chronic hip joint pain. Conclusion: Hip frontal plane motion was greater in those with chronic hip joint pain compared to those with patellofemoral pain. In both groups, greater abnormal movement at the respective joint (e.g., knee external rotation in the patellofemoral pain group and hip adduction and internal rotation in the chronic hip joint pain group) was associated with greater pain at that joint during a single-limb squat. Keywords: Anterior knee pain syndrome, Femoroacetabular impingement, Hip joint, Kinematics, Knee joint, Single-limb squat